Curcuit board application to additive manufactured components by laser-direct-structuring - Gath, Christian; Drummer, Dietmar (2016 12th International Congress Molded Interconnect Devices (MID), 2016)
With the demand for complex, individualized and functionalized products with respect to constantly decreasing life cycles, additive manufacturing processes such as the process of selective laser sintering (SLS) has increasingly been of industrial interest. These processes are being used more and more to produce models, prototypes and partially finished products made of plastic, metal or ceramic and require neither a tool nor a form. Affected by decreasing installation spaces and increasing functional densities, flexible methods for circuit board application and their combination with additive manufacturing are in the focus of electronic industry research activities. In the context of this article both a thermoplastic polymer polybutylene terephthalate (PBT) which has been prepared to defined powder fractions with cryogenic milling, and the established and commercially available SLS material (PA12, PA2200) were the subject of a dry coating process with LDSadditives. Subsequently, these LDS-powders were processed with SLS to form test specimens. Finally their surface was structured and metallized through the LPKF-LDS-process (Laser-Direct- Structuring). Based on these metallized specimens, the metallization was studied as a function of an LDS-additive filling ratio. To uncover positive synergy effects from additively manufacturing the polymer body, the metallization was analyzed in terms of shape and adhesive strength.